2017
DOI: 10.1038/srep40153
|View full text |Cite
|
Sign up to set email alerts
|

Di2-ethylhexyl phthalate disrupts thyroid hormone homeostasis through activating the Ras/Akt/TRHr pathway and inducing hepatic enzymes

Abstract: Di(2-ethylhexyl) phthalate (DEHP), as a widespread environmental pollutant and an endocrine disruptor, can disturb the homeostasis of thyroid hormones (THs). In order to elucidate roles of the MAPK and PI3K/Akt pathways and hepatic enzymes in thyroid-disrupting effects of DEHP, Sprague-Dawley rats were dosed with DEHP by gavage for 30 consecutive days; Nthy-ori 3-1 cells were treated with DEHP with NAC, k-Ras siRNA or inhibitors (U0126 and wortmannin). Results showed that DEHP led to histopathologic changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 35 publications
3
44
0
7
Order By: Relevance
“…The results indicate that TRHr is modulated by the p38 pathway in the present study. It is shown that abnormal expressions of hormone receptors would interfere with the normal hormone signal transduction in the HPT axis and subsequently disturb TH homeostasis [4]. In our current study, T4 and T3 levels in plasma were reduced and the magnitude of observed hypothyroidism is consistent with previous studies in rats [5, 7], whereas TSH and TRH were not increased as expected to compensate decrements in THs, suggesting impairments of the negative feedback system of the HPT axis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results indicate that TRHr is modulated by the p38 pathway in the present study. It is shown that abnormal expressions of hormone receptors would interfere with the normal hormone signal transduction in the HPT axis and subsequently disturb TH homeostasis [4]. In our current study, T4 and T3 levels in plasma were reduced and the magnitude of observed hypothyroidism is consistent with previous studies in rats [5, 7], whereas TSH and TRH were not increased as expected to compensate decrements in THs, suggesting impairments of the negative feedback system of the HPT axis.…”
Section: Discussionsupporting
confidence: 91%
“…Even small changes or an imbalance in thyroid homeostasis may adversely affect human health. Especially for children, the disturbance of thyroid homeostasis during nervous system development would lead to irreversible mental retardation [4]. Therefore, disturbing factors of thyroid homeostasis are of great concern.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, phthalates can affect thyroid hormones not only through biosynthesis and biotransport but also through biotransformation and metabolism (Liu et al 2015). Recent animal experiments have suggested that DEHP can influence thyroid hormones by disturbing the hypothalamus-pituitary-thyroid axis (Dong et al 2017) and activating the Ras-Aktthyrotropin-releasing hormone receptor pathway and inducing hepatic enzymes (Ye et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on elderly people suggest that insulin resistance is increased after DEHP exposure due to an imbalance between oxidative stress production and antioxidant defenses, as DEHP is known to induce oxidative stress, which might also lead to insulin resistance in elderly people [ 28 ]. DEHP can disturb thyroid hormone homeostasis and reduce TH levels [triiodothyronine (T3), thyroxine (T4), and thyrotropin-releasing hormone (TRH) can be reduced] by activating the Ras/Akt/TRHr pathway and affect hepatic enzymes that play vital roles in thyroid-disrupting effects [ 29 ].…”
Section: Dehp and Endocrine Toxicitymentioning
confidence: 99%